Inverted U wave & de Winter pattern: under-recognized sign of acute coronary occlusion - Maulana, Zaky Faris; Napu, Ramang (The Indonesian Heart Association, 2025)
Background: Interpreting ECGs for evidence of ischemia in patients with noticeable changes, such as ST-segment elevation and ST-segment depression, can be easily identified. However, identifying & recognizing atypical ECG patterns of acute coronary syndrome is essential in preventing significant mortality and morbidity. In thefollowing case report, we describe inverted U wave & de Winter pattern. Case Illustration: A 58-year-old male presented to the emergency department with pressure-like chest pain. His initial evaluation revealed normal blood pressure and elevated blood glucose levels, and an initial ECG was incorrectly interpreted as normal. Eight hours later, he returned with worsened chest pain. The new ECG revealed the de Winter ECG pattern, which indicates acute occlusion of the left anterior descending artery. Additionally, previously overlooked inverted U waves in the initial ECG suggested myocardial ischemia.Eventually, the angiography revealed a complete occlusion of the proximal left anterior descending coronary artery. The patient underwent stent placement and have a good outcome Conclusions: Inverted U wave and the de Winter pattern described in this case indicates an acute LAD occlusion. It’s a rare finding, but it is critical for emergency physicians to recognize it for urgent reperfusion therapy. Unfamiliarity with these high-risk ECG pattern may lead to delays in appropriate treatment, causing negative effects on morbidity and mortality.